Antiseptic Skin Agents to Prevent Surgical Site Infection After Incisional Surgery: A Randomized, Three-armed Combined Non-inferiority and Superiority Clinical Trial (NEWSkin Prep Study). Issue 5 (8th May 2022) - Smith, Stephen Ridley; Gani, Jon; Carroll, Rosemary; Lott, Natalie; Hampton, Jacob; Oldmeadow, Christopher; Clapham, Mathew; Attia, John
Abstract : Objective: To compare SSI rates between the skin preparation agents: PI-Aq, povidone-iodine with alcohol (PI-Alc), and chlorhexidine with alcohol (C-Alc). Background: Guidelines suggest that alcohol-containing chlorhexidine solutions are the gold standard for skin preparation before surgery. It remains difficult to determine whether it is the chlorhexidine component or the addition of alcohol that confers the most benefit. Methods: We conducted a multicenter, prospective, combined non-inferiority (PI-Alc vs C-Alc) and superiority (PI-Alc vs PI-Aq) randomized clinical trial. Participants were randomized 1:1:1 to receive either C-Alc, PI-Alc, or PI-Aq. The primary outcome was SSI rate as defined by the Centers for Disease Control. Secondary outcomes were complication rates, length of hospital stay, readmissions, and skin reactions. Results: Between January 2015 and December 2018, 3213 patients were randomized (C-Alc: 1076, PI-Alc: 1075, and PI-Aq: 1062). Mean age of participants was 57% and 55% were female. SSI rates were: C-Alc 11.09%, PI-Alc 10.88%, and PI-Aq 12.56%. PI-Alc was found to be non-inferior to C-Alc (mean difference, −0.21%; 95% confidence interval, −2.85 to 2.44; P = 0.0009 non-inferiority), whereas PI-Alc was not superior to PI-Aq (mean difference, −1.68%; 95% confidence interval, −4.40 to 1.05; P = 0.2302). There were no differences seen in secondary outcomes between groups and no treatment related adverse events or deaths occurred. Conclusions: PI-Alc is non-inferior to C-Alc and not superior to PI-Aq. This is at odds with current guidelines that suggest alcohol-based chlorhexidine solutions should routinely be used for surgical skin preparation. Trial Registration: Australia and New Zealand Clinical Trials Registry: ANZCTRN12615000021571. www.anzctr.org.au